Uma avaliaç\~ao de impacto de um programa de qualificaç\~ao profissional na empresa sobre a inserç\~ao dos jovens no mercado de trabalho formal - Carlos Henrique Corseuil; Miguel N. Foguel; Leon Faceira Tomelin (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– In this paper, we evaluate the impact of a qualification program for young people in which training is fully offered by a group of potential employers. We perform this evaluation comparing such initiative to the Jovem Aprendiz Program, whose participants make up a pertinent control group in order to measure the effects of the differentiated training provided by the studied program. Using methods based on propensity score matching and Rais data, we investigate the placement of those young people in the labor market after the period of participation in the respective programs. Our results indicate that participation in the training program positively affects the employability of youngsters, having an impact on obtaining formal employment and in larger companies (in number of employees) and that pay higher average wages. Regarding the remuneration of the participants, the results suggest no effect in the short term and negative effects in the medium term, compared to the participants of the Jovem Aprendiz Program.
Keywords: J13; J24; J38; 330; training; youth; labor market